8-Nitroguanine, a Potential Biomarker to Evaluate the Risk of Inflammation-Related Carcinogenesis - Ma, Ning; Murata, Mariko; Ohnishi, Shiho; Thanan, Raynoo; Hiraku, Yusuke; Kawanishi, Shosuke (IntechOpen, 2012)
None